UJI DAYA HAMBAT FRAKSI n-HEKSAN EKSTRAK ETANOL BUAH TOMAT (Lycopersicum esculentum Mill.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - sernita sernita (Jurnal Analis Kesehatan Kendari, 2022)
Tomato (Lycopersicumesculentum Mill.) Is a vegetable plant that plays an important role in meeting community nutrition. In addition, tomatoes can also be used as medicine. The chemical content of tomatoes such as alkaloids, saponins can be as antibacterial. This study was conducted to determine whether the n-hexane fraction of tomato fruit extracts could inhibit the growth of Staphylococcus aureus bacteria. This research was conducted experimentally, tomato fruit was extracted by maceration method using ethanol 96% solvent then fractionated by partitioning method using n-hexane solvent. The n-hexane fraction was then made in concentrations of 10%, 15% and 20% with ampisillin as a positive control and distilled water as a negative control, tested using the wells method. The results showed that the n-hexane fraction of tomato fruit extract could inhibit the growth of Staphylococcus aureus bacteria with an average diameter of inhibitory zone at a concentration of 10% at 16,0 mm, a concentration of 15% at 17,4 mm and a concentration of 20% at 17,7 mm and ampisillin positive control at 27,9 mm. From the results of the One Way Anova test obtained sig value <0.05 which means that the n-hexane fraction of tomato extract with 3 repetitions of each treatment showed that the average treatment had a significant effect on the growth of Staphylococcus aureus bacteria. Keywords: Tomato Fruit, n-hexane fraction, Staphylococcus aureus.